2020
DOI: 10.1002/jsid.922
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ion impurity in thermally activated delayed fluorescence organic light‐emitting diode materials and device lifetime

Abstract: We propose a measurement method of ion impurity amounts of thermally activated delayed fluorescence (TADF) green dopant powders in a solution by applying a triangle voltage waveform and measuring a small displacement current that has been developed for screening and optimization of materials for thin‐film transistor‐liquid crystal displays (TFT‐LCDs). We found that there is a strong correlation between ion impurity and organic light‐emitting diode (OLED) lifetime, and we confirmed that the TADF green dopant, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The LC was non-polar liquid crystal, NA-1345 (DIC Corporation, Japan). The measurement conditions of DCM were set to 10 mHz of triangular wave voltage signal with ±10 V of applied voltage [10]. The I-V characteristics were measured three times at the temperature of 60 °C.…”
Section: Dcm Of a Mixture Of Liquid Crystal And An Organic Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The LC was non-polar liquid crystal, NA-1345 (DIC Corporation, Japan). The measurement conditions of DCM were set to 10 mHz of triangular wave voltage signal with ±10 V of applied voltage [10]. The I-V characteristics were measured three times at the temperature of 60 °C.…”
Section: Dcm Of a Mixture Of Liquid Crystal And An Organic Compoundmentioning
confidence: 99%
“…Inoue et al also have demonstrated to evaluate the behavior of lithium-fluoride (LiF) in OLEDs by DCM [9]. Recently, DCM was employed to detect the amount of ionic impurities in a solution of thermally activated delayed fluorescence (TADF) green emitting material, which was dissolved in xylene and filled into an LC cell [10]. It was realized that xylene contains many ionic impurities so it was difficult to accurately evaluate the amount of ions contained in the TADF emitter.…”
Section: Introductionmentioning
confidence: 99%